2010
DOI: 10.1186/1744-8069-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Primary Afferent Activity following Inferior Alveolar Nerve Transection in Rats

Abstract: BackgroundIn order to evaluate the neural mechanisms underlying the abnormal facial pain that may develop following regeneration of the injured inferior alveolar nerve (IAN), the properties of the IAN innervated in the mental region were analyzed.ResultsFluorogold (FG) injection into the mental region 14 days after IAN transection showed massive labeling of trigeminal ganglion (TG). The escape threshold to mechanical stimulation of the mental skin was significantly lower (i.e. mechanical allodynia) at 11-14 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 70 publications
2
40
0
Order By: Relevance
“…In particular, the intrathecal reuptake inhibition approach would not be expected to influence peripherally generated afferent activity from nociceptors, 10 which has been shown to be present for several weeks after nerve injury and may play a role in re-establishing central sensitisation. 34,40 Similar findings have been reported with systemic dosing of TCAs where mechanical allodynia persisted after the cessation of dosing although other measures of evoked sensitisation were attenuated. 1 It is conceivable that continuation of intrathecal dosing beyond the period of altered peripheral afferent input could prevent the subsequent development of sensitisation although this may also require that aberrant afferent barrages from the periphery have ceased in the meanwhile.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In particular, the intrathecal reuptake inhibition approach would not be expected to influence peripherally generated afferent activity from nociceptors, 10 which has been shown to be present for several weeks after nerve injury and may play a role in re-establishing central sensitisation. 34,40 Similar findings have been reported with systemic dosing of TCAs where mechanical allodynia persisted after the cessation of dosing although other measures of evoked sensitisation were attenuated. 1 It is conceivable that continuation of intrathecal dosing beyond the period of altered peripheral afferent input could prevent the subsequent development of sensitisation although this may also require that aberrant afferent barrages from the periphery have ceased in the meanwhile.…”
Section: Discussionsupporting
confidence: 73%
“…1 It is conceivable that continuation of intrathecal dosing beyond the period of altered peripheral afferent input could prevent the subsequent development of sensitisation although this may also require that aberrant afferent barrages from the periphery have ceased in the meanwhile. 34,40 The use of systemic monoamine reuptake inhibitors is established as a therapeutic strategy for chronic pain in general and neuropathic pain in particular. 4,41 Animal studies have shown that such systemic dosing increases NA levels in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…A cell area >1000 µm 2 was considered large, while that <1000 µm 2 was considered medium and <400 µm 2 was considered small [20].…”
Section: Methodsmentioning
confidence: 99%
“…46,47 Mechanical hypersensitivity accompanying trigeminal neuropathic pain involves spontaneous and low-threshold activity in injured myelinated fibers. 48 Animal models of trigeminal neuropathic pain consistently produce facial mechanical allodynia and central sensitization manifested by a reduced activation threshold and increased response to noxious and innocuous stimuli of medullary dorsal horn nociceptive neurons. 49 Thus, the spontaneous headache episodes, as well as the cranial allodynia and hyperalgesia seen in individuals with CPTHA, 17 may result from pathological changes in the cranial nerves.…”
Section: Peripheral Originmentioning
confidence: 99%